Nano preparation based on ferrous phosphide nano structure as well as preparation method and application of nano preparation

By using nano-formulations based on ferrous phosphide nanostructures, combined with PTMP-PMAA polymers and glucose oxidase, the therapeutic bottleneck of PDT in the tumor microenvironment has been overcome, achieving improvement of the tumor microenvironment, synergistic enhancement of multiple therapies, and real-time imaging, thereby improving the precision and safety of tumor treatment.

CN121422211APending Publication Date: 2026-01-30HARBIN MEDICAL UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202512034189.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-31
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Current photodynamic therapy (PDT) in cancer treatment is limited by the complexity of the tumor microenvironment, including hypoxia, the antioxidant barrier of glutathione (GSH) to clear ROS, difficulty in clearing tumor stem cells, and lack of real-time imaging guidance, resulting in poor treatment efficacy and insufficient safety.

Method used

By employing ferrous phosphide nanostructures, and by surface modification of PTMP-PMAA polymers and loading glucose oxidase, multifunctional nanotherapeutic agents are constructed to improve the tumor microenvironment, enhance the synergistic effects of multiple therapies, and provide real-time imaging guidance, including chemokinetic therapy, photothermal therapy, and starvation therapy.

Benefits of technology

It significantly improves the efficacy of tumor treatment, effectively eliminates tumor cells and targets tumor stem cells, reduces the risk of recurrence, and achieves precise positioning and monitoring through T2-weighted magnetic resonance imaging and near-infrared photoacoustic imaging, while possessing excellent biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121422211A_ABST
    Figure CN121422211A_ABST
Patent Text Reader

Abstract

The invention relates to a nano preparation based on a ferrous phosphide nano structure and a preparation method and application thereof, and belongs to the technical field of medical nano materials. In order to solve the problems that in the prior art, the curative effect of CDT is limited, the single therapy effect is poor, and effective imaging guidance lacks, the invention provides a nano preparation based on a ferrous phosphide nanostructure, the nano preparation comprises a core layer, a modification layer and a functional layer, the core layer is a hydrophobic ferrous phosphide nanostructure, the modification layer is a PTMP-PMAA polymer, and the functional layer is glucose oxidase. The nano preparation disclosed by the invention induces tumor apoptosis by increasing the ROS level through multiple synergy of chemical kinetics therapy, hunger therapy and photothermal therapy, so that the tumor treatment effect is remarkably improved; the system also has the advantages of precise dual-mode imaging and biological safety, can precisely position the tumor boundary, monitors the distribution and treatment process of the preparation in the tumor, provides a reliable basis for the selection of treatment opportunities, and shows important application prospects in the field of precise tumor treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical nanomaterials technology, and particularly relates to nano-preparations based on ferrous phosphide nanostructures, their preparation methods and applications. Background Technology

[0002] Photodynamic therapy (PDT) uses photosensitizers to generate reactive oxygen species (ROS) under specific light irradiation to kill tumors. It boasts advantages such as strong targeting, minimal invasiveness, and low toxicity, making it a highly promising tumor treatment strategy with good prospects in the palliative treatment of early-stage superficial and metastatic tumors. However, the efficacy of PDT is limited by the complexity of the tumor microenvironment (TME) and the reliance on single-method approaches. Key issues include: first, rapid tumor proliferation and vascular malformations leading to hypoxia severely limit the efficiency of ROS generation by photosensitizers; second, excessive glutathione (GSH) in the TME can scavenge ROS, forming an antioxidant barrier, and existing oxygen supplementation methods, such as natural catalase (CAT), exhibit poor stability and activity decay in the acidic environment of the tumor, resulting in limited oxygenation effects; and third, PDT alone is insufficient to eliminate tumor stem cells, easily leading to recurrence and metastasis, and lacks real-time imaging guidance, making it impossible to accurately locate tumor boundaries and monitor treatment progress, resulting in insufficient safety and precision.

[0003] While current research attempts to combine PDT with other therapies, existing approaches suffer from loose synergistic mechanisms and insufficient functional integration. No integrated, multifunctional nanotherapeutic agents have yet been developed that can simultaneously improve hypoxia, deplete GSH, enhance the synergistic effects of multiple therapies, and integrate real-time imaging guidance. Therefore, developing nanotherapeutic agents that adapt to the characteristics of the tumor microenvironment and achieve full-chain integration of "imaging guidance-microenvironment regulation-synergistic therapy" is crucial for overcoming the bottlenecks in PDT treatment and improving the precision and effectiveness of tumor therapy. Summary of the Invention

[0004] To address the limitations of CDT efficacy, poor efficacy of single therapy, and lack of effective imaging guidance in existing technologies, this invention provides nano-formulations based on ferrous phosphide nanostructures, their preparation methods, and applications.

[0005] The technical solution of this invention:

[0006] A nano-formulation based on ferrous phosphide nanostructures includes a core layer, a modification layer, and a functional layer. The core layer is a hydrophobic ferrous phosphide nanostructure. The modification layer is a PTMP-PMAA (polytrimethylolpropane-polymethacrylic acid) polymer coated on the surface of the hydrophobic ferrous phosphide nanostructure. The functional layer is glucose oxidase, which is covalently grafted onto the surface of the PTMP-PMAA polymer modification layer via an amidation reaction.

[0007] Furthermore, the hydrophobic ferrous phosphide nanostructure is a nanorod, the length of which is 150~200nm and the diameter is 8~15nm.

[0008] A method for preparing nano-formulations based on ferrous phosphide nanostructures, comprising the following steps:

[0009] Step 1: Preparation of hydrophobic ferrous phosphide nanostructures:

[0010] Ferric acetylacetone was dissolved in oleylamine solvent, and the nanostructure was grown at the first heating temperature under inert gas protection. Then, trioctylphosphine was added, and the temperature of the reaction system was raised to the second heating temperature to continue the reaction, thus obtaining hydrophobic ferrous phosphide nanostructures.

[0011] Step 2: Preparation of PTMP-PMAA polymer:

[0012] Under inert gas protection, methacrylic acid, anhydrous ethanol and pentaerythritol tetra-3-mercaptopropionate were stirred and dissolved. After heating to the third heating temperature, a free radical initiator was added to initiate the copolymerization reaction. After the reaction was completed, the product was concentrated, precipitated and vacuum dried to obtain the PTMP-PMAA polymer.

[0013] Step 3: Preparation of nano-formulations loaded with glucose oxidase:

[0014] The hydrophobic ferrous phosphide nanostructures obtained in step one and the PTMP-PMAA polymer obtained in step two were co-dispersed in anhydrous ethanol, ultrasonicated and stirred overnight, and centrifuged to obtain PTMP-PMAA polymer-coated ferrous phosphide nanostructures.

[0015] The obtained PTMP-PMAA polymer-coated ferrous phosphide nanostructures were dispersed in MES buffer solution with a pH of 5.0-5.5, and carbodiimide and N-hydroxythiosuccinimide salt were added. The pH of the system was then adjusted to 7.0-8.0 and glucose oxidase was added. The mixture was stirred overnight under ice bath conditions and centrifuged to obtain the glucose oxidase-loaded nanoformulation.

[0016] Furthermore, in step one, the molar ratio of acetylacetone iron to trioctylphosphine is 1:8~12; when preparing ferrous phosphide nanorods, the mass-volume ratio of acetylacetone iron to oleylamine solvent is 3.0~4.0 mg:1 mL, and the oleylamine solvent is added in two equal volumes.

[0017] Furthermore, in step one, the first heating temperature is 250~270℃, and the growth time of the nanostructure is 0.8~1.2h; the second heating temperature is 310~330℃, and the reaction time at the second heating temperature is 2~3h.

[0018] Furthermore, in step two, the molar ratio of methacrylic acid and pentaerythritol tetra-3-mercaptopropionate is 60~80:1, and the mass-to-volume ratio of the total mass of methacrylic acid and pentaerythritol-3-mercaptopropionate to the mass-to-volume ratio of anhydrous ethanol is 0.10~0.15mg:1mL.

[0019] The free radical initiator is azobisisobutyronitrile, and the amount of azobisisobutyronitrile is 0.5~0.2% of the total molar amount of methacrylic acid and pentaerythritol-3-mercaptopropionate; the third heating temperature is 70~80℃.

[0020] Furthermore, in step three, the mass-to-volume ratio of the hydrophobic ferrous phosphide nanostructure, the PTMP-PMAA polymer, and anhydrous ethanol is 1 mg:0.5~2 mg:5 mL; the ultrasonic power is 80~120 W, and the ultrasonic time is 4~6 h.

[0021] Furthermore, in step three, the mass-to-volume ratio of the PTMP-PMAA polymer-coated ferrous phosphide nanostructure to the MES buffer is 0.5~2 mg:1 mL; the amount of carbodiimide added is 10 mM, and the amount of N-hydroxythiosuccinimide salt added is 5 mM; the final concentration of glucose oxidase in the reaction system is 1~3 mg / mL.

[0022] The present invention relates to the application of a nano-formulation based on ferrous phosphide nanostructure in the preparation of a tumor synergistic therapy formulation or an MRI / PAI contrast agent.

[0023] Furthermore, the tumor synergistic therapy includes photothermal therapy, chemokinetic therapy, or starvation therapy.

[0024] The beneficial effects of this invention are:

[0025] This invention utilizes ferrous phosphide (Fe2P) nanostructures as the core, and constructs multifunctional nanotherapeutic agents by surface modification with PTMP-PMAA polymer and loading glucose oxidase (GOx). In this agent, Fe2P exhibits both Fenton-like catalytic activity and photothermal conversion capabilities, catalyzing the conversion of H2O2 into highly toxic ·OH, and generating a mild thermal effect of 40-45°C under near-infrared light irradiation. The PTMP-PMAA polymer significantly enhances the system's stability while providing protective loading sites for GOx. GOx achieves "starvation therapy" by consuming tumor glucose and generates H2O2 in situ to supply the Fe2P catalytic reaction, forming a cascade amplification effect of "glucose consumption - H2O2 generation - ·OH production." Fe2P-mediated Fe... 2+ / Fe 3+Cyclic activity can deplete excess glutathione (GSH) within tumors, disrupting their antioxidant defense system, while a mild thermal effect synergistically accelerates reaction kinetics and enhances GOx activity. The nano-formulation provided by this invention induces tumor apoptosis through a synergistic effect of chemokinetic therapy, starvation therapy, and photothermal therapy, significantly improving tumor treatment efficacy. It not only effectively eliminates tumor cells but also targets tumor stem cells, substantially reducing the risk of recurrence.

[0026] Meanwhile, the specific structure of the multifunctional nanotherapeutic formulation provided by this invention gives it advantages in precise imaging and biosafety. The Fe2P nanostructure itself possesses excellent T2-weighted magnetic resonance imaging (T2-MRI) performance and near-infrared photoacoustic imaging (PAI) signals, enabling dual-mode imaging without the need for additional contrast agents. This allows for precise localization of tumor boundaries, monitoring of formulation distribution within the tumor, and monitoring of treatment progress, providing a reliable basis for selecting the timing of treatment. The introduction of the PTMP-PMAA polymer significantly improves the biocompatibility of the formulation and reduces the potential toxicity of the Fe2P nanomaterials. Acute and subacute toxicity experiments have confirmed that at therapeutic doses, the formulation does not cause significant damage to major organs in experimental animals and has no systemic toxicity. Its excellent imaging capabilities and biosafety provide a solid foundation for its clinical translation and demonstrate significant application prospects in the field of precision oncology. Attached Figure Description

[0027] Figure 1 The images are microscopic images of Fe2PNRs and FGNRs prepared in Example 1. A is a transmission electron micrograph of Fe2PNRs prepared in step one, and B is a high-resolution transmission electron micrograph of FGNRs.

[0028] Figure 2 The X-ray diffraction pattern and elemental mapping diagram of the FGNRs prepared in Example 1 are shown in Figure A, where A is the X-ray diffraction pattern and B is the elemental mapping diagram of Fe, P, and O.

[0029] Figure 3 The particle size distribution and zeta potential diagrams of Fe2PNRs, FPNRs and FGNRs prepared in Example 1 are shown in Figure A, where A is the particle size distribution diagram and B is the zeta potential diagram.

[0030] Figure 4 The following is a comprehensive characterization diagram of the photothermal performance of FGNRs in the photothermal performance test of Example 2: A is a comparison diagram of the temperature change curves of FGNRs under different laser power densities, B is a diagram of the photothermal stability cycle test results of FGNRs, and C is a diagram of the heating-cooling curve of FGNRs.

[0031] Figure 5The environmental response characteristics of FGNRs in glucose solution during the catalytic performance test in Example 2 are shown in Figure A, which is a comparison of the pH value change curves of FGNRs in glucose solution at different temperatures, and Figure B is the ESR spectrum of FGNRs in glucose solution at different pH values.

[0032] Figure 6 The following are characterization diagrams of the effects of H2O2, glucose, and temperature on the ESR and fluorescence properties of FGNRs in the catalytic performance test of Example 2. A is the ESR spectrum of FGNRs with and without added H2O2 and glucose; B is the ESR spectrum of FGNRs in glucose solutions at different temperatures; C is the fluorescence spectrum of FGNRs in glucose solutions at different temperatures.

[0033] Figure 7 This is a comparison of cell viability of HK-2, HEK-293, OS-RC-2 and 786-O cells after treatment with different concentrations of FPNRs in Example 3;

[0034] Figure 8 This is a comparison of cell viability of OS-RC-2 and 786-O under different treatment conditions in Example 3;

[0035] Figure 9 The following are comparison charts showing the survival rates of OS-RC-2 cells under different pH or glucose concentrations in Example 3: A is a comparison chart of survival rates under different pH conditions; B is a comparison chart of survival rates under different glucose concentrations.

[0036] Figure 10 The graph shows the Calcein-AM / PI fluorescence spectra and statistical analysis comparison of OS-RC-2 cells in different treatment groups in Example 3. A is the fluorescence spectrum, and B is the comparison of the ratio of live to dead cells.

[0037] Figure 11 This is a comparison of fluorescence images and statistical analysis of reactive oxygen species (ROS) produced by OS-RC-2 cells in different treatment groups in Example 3. A is a fluorescence image, and B is a comparison of median fluorescence intensity.

[0038] Figure 12 The images show infrared thermal images and temperature change curves of mice in the NIR group and FGNRs+NIR group at different time intervals in Example 4. A is the infrared thermal image and B is the temperature change curve comparison.

[0039] Figure 13 This is a graph showing the weight change of mice in each group in Example 4;

[0040] Figure 14 This is a comparison chart of the changes in tumor volume and weight of mice in each group in Example 4 over time. A represents tumor volume, and B represents tumor weight.

[0041] Figure 15 These are images of tumors isolated from mice in each group 14 days after treatment in Example 4.

[0042] Figure 16 Comparison of H&E staining, TUNEL staining, and Ki-67 staining of mouse tumor tissues in each group in Example 4;

[0043] Figure 17 The images shown are in vitro T2-weighted MRI images and corresponding T2 relaxation rate curves of FGNRs dispersions at different Fe concentrations in Example 5. A is a T2-weighted image, and B is a T2 relaxation rate curve.

[0044] Figure 18 The figures show in vitro acousto-optic imaging of the FGNRs dispersion at 808 nm wavelength in Example 5 and the linear relationship between the acousto-optic amplitude and the FGNRs concentration. A is the acousto-optic imaging and B is the linear relationship graph.

[0045] Figure 19 The figures show in vitro acousto-optic imaging of the FGNRs dispersion at a wavelength of 1064 nm and the linear relationship between the acousto-optic amplitude and the FGNRs concentration in Example 5. A is the acousto-optic imaging and B is the linear relationship graph.

[0046] Figure 20 These are T2-weighted magnetic resonance images of tumor mice before and after intravenous injection and intratumoral injection of FGNRs in Example 5.

[0047] Figure 21 The images shown are acoustic-optical images and acoustic-optical amplitude change curves at different time points after intratumoral injection of FGNRs in Example 5. A is the acoustic-optical image, and B is the acoustic-optical amplitude change curve.

[0048] Figure 22 The images shown are acoustic-optic imaging and acoustic-optic amplitude change curves at different time points after intravenous injection of FGNRs in Example 5. A represents the acoustic-optic imaging, and B represents the acoustic-optic amplitude change curve. Detailed Implementation

[0049] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. In the following embodiments, the process equipment or apparatus not specifically specified are all conventional equipment or apparatus in the art. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0050] Example 1

[0051] This embodiment provides a method for preparing ferrous phosphide nanorods loaded with glucose oxidase.

[0052] The preparation method of ferrous phosphide nanorods loaded with glucose oxidase in this embodiment is as follows:

[0053] Step 1: Preparation of ferrous phosphide nanorods (Fe2PNRs):

[0054] 0.1765 g of acetylacetone iron as the iron source was dissolved in 25 mL of oleylamine and heated to 260 °C under nitrogen protection. Another 25 mL of oleylamine was then quickly added to the system, and the mixture was kept at this temperature for 1 h to complete the growth of the nanorods. Then, 5 mL of trioctylphosphine as the phosphorus source was injected, and the temperature was raised to 320 °C to continue the reaction for 2.5 h. After the reaction was completed, the product was collected by centrifugation and washed with cyclohexane to obtain ferrous phosphide nanorods Fe2PNRs.

[0055] Step 2: Preparation of PTMP-PMAA polymer:

[0056] Under nitrogen protection, 8.166 g of methacrylic acid, 75 mL of anhydrous ethanol, and 0.9165 g of pentaerythritol tetra-3-mercaptopropionate as a crosslinking agent were placed in a reaction flask and stirred to dissolve. The temperature was raised to 75 °C, and 150 mg of azobisisobutyronitrile (AIBN) free radical initiator was quickly added to initiate the copolymerization reaction. After the reaction was completed, the product was concentrated by rotary evaporation, precipitated with anhydrous diethyl ether, and dried under vacuum to obtain a white powder of PTMP-PMAA polymer.

[0057] Step 3: Preparation of ferrous phosphide nanorods (FGNRs) loaded with glucose oxidase:

[0058] 20 mg of Fe2PNRs nanorods prepared in step one and 24 mg of PTMP-PMAA polymer prepared in step two were dispersed together in 100 mL of anhydrous ethanol. After ultrasonic treatment at 100 W for 5 h and stirring overnight, Fe2P@PTMP-PMAA nanorods were obtained by centrifugation and denoted as FPNRs.

[0059] 3.0 mg of the obtained PTMP-PMAA polymer-coated Fe2PNRs nanorods were dispersed in 2.0 mL of MES (2-(N-morpholino)ethanesulfonic acid) buffer at pH 5.2. 3.84 mg of carbodiimide was added to bring the concentration to 10 mM, and 2.2 mg of N-hydroxythiosuccinimide salt was added to bring the concentration to 5 mM to activate the carboxyl groups on the PTMP-PMAA polymer backbone. Subsequently, the pH of the system was adjusted to 7.4, and glucose oxidase was added to bring the final concentration in the reaction system to 2 mg / mL. The coupling reaction was carried out overnight under ice bath conditions with stirring. After centrifugation, ferrous phosphide nanorods (FGNRs) loaded with glucose oxidase were obtained.

[0060] This embodiment further characterizes the products Fe2PNRs, FPNRs, and FGNRs from each step.

[0061] Figure 1 Microscopic images of Fe2PNRs and FGNRs. Figure 1 A shows that Fe2PNRs have a rod-like structure with a length of 174.8 ± 16.2 nm and a cross-sectional diameter of 10.9 ± 2.9 nm. Figure 1 B shows that FGNRs have a crystal structure with a lattice spacing of 0.205 nm. This is consistent with the 201 crystal plane of Fe2P, proving the successful synthesis of Fe2P.

[0062] Figure 2 The X-ray diffraction pattern and elemental mapping diagrams of FGNRs are shown. Figure 2 As shown in Figure A, the diffraction peaks of the upper FGNRs match the peak positions and intensities of the lower hexagonal ferrous phosphide Fe2P standard card JCPDS85-1727, proving the successful synthesis of ferrous phosphide nanorods. Figure 2 B shows that FGNRs uniformly contain Fe, P, and O elements, with the O element mainly derived from the carboxyl group of the PTMP-PMAA polymer and the protein structure of GOx, confirming the success of polymer coating and enzyme loading.

[0063] Figure 3 The particle size distribution and zeta potential diagrams for Fe2PNRs, FPNRs, and FGNRs are shown. Figure 3 A shows that after modification with PTMP-PMAA and glucose oxidase, the sizes of FPNRs and FGNRs gradually increased. Figure 3 B shows that the zeta potential decreases after PTMP-PMAA coating, but increases after glucose oxidase loading. This trend is consistent with the surface charge regulation rules of polymer carboxyl group introduction and enzyme protein molecule grafting, further verifying the successful construction of the nano-formulation hierarchical structure.

[0064] Example 2

[0065] This embodiment examines the in vitro photothermal and catalytic properties of the ferrous phosphide nanorods (FGNRs) loaded with glucose oxidase prepared in Example 1.

[0066] I. Photothermal Performance Testing

[0067] The ferrous phosphide nanorods (FGNRs) loaded with glucose oxidase prepared in Example 1 were dispersed in deionized water to prepare an aqueous solution with a concentration of 100 ppm. The solution was ultrasonically dispersed for 10 min to ensure uniformity and stability and to avoid particle aggregation.

[0068] Set the infrared thermal imager to normal operating condition and align its detection probe with the center area of ​​the sample container to ensure that the detection range completely covers the sample liquid surface; focus the output spot of the 1064nm near-infrared laser on the center of the sample and adjust the distance between the laser and the sample to ensure that the spot uniformly covers the sample surface.

[0069] (1) Detect the temperature change of FGNRs under different laser power densities.

[0070] The laser power density was set to 0.15 W / cm². 2 0.3W / cm 2 0.5W / cm 2 0.75W / cm 2 and 1W / cm 2 Three parallel experiments were set up for each power density group. 3 mL of the above FGNRs aqueous solution was placed in a quartz cuvette, placed on the detection platform, and allowed to stand for 5 min to allow the solution temperature to reach room temperature (25℃) and stabilize. The laser was turned on, and the infrared thermal imager was started simultaneously to record the temperature in real time. The sampling interval was 10 s, and the irradiation was continued for 10 min. The temperature change curves of the FGNRs aqueous solution under different power densities were plotted with time as the x-axis and temperature as the y-axis.

[0071] The results are as follows Figure 4 As shown in Figure A, the heating effect of the FGNRs aqueous solution is positively correlated with the laser power density, especially when the power density is ≥0.5 W / cm². 2 At that time, the system temperature can reach the effective temperature range of photothermal therapy of 40-45℃.

[0072] (2) Detect the photothermal stability of FGNRs.

[0073] The laser power density was fixed at 0.3 W / cm². 2 To ensure stable device parameters, 3 mL of a 100 ppm FGNRs aqueous solution was placed in a quartz cuvette and allowed to stand until it stabilized at room temperature before starting the experiment. The laser on / off time was set to 600 s, and the on / off time to 600 s. One cycle consisted of five cycles. From the moment the laser was turned on in the first cycle, the infrared thermal imager recorded the sample temperature in real time at 10-s intervals until the temperature stabilized after the laser was turned off in the fifth cycle, with a total recording time of 6000 s. The temperature change curve of the FGNRs aqueous solution during the five laser on / off cycles was plotted with time on the x-axis and temperature on the y-axis.

[0074] The results are as follows Figure 4As shown in Figure B, after five cycles of laser irradiation and shutdown, the FGNRs aqueous solution rapidly heated to a similar temperature plateau each time the laser was turned on, and the temperature quickly dropped back to the initial level after the laser was turned off. The temperature change between each cycle was less than 2°C, indicating that the nano-formulation has excellent photothermal stability and can maintain stable photothermal performance during multiple photothermal conversions, providing a reliable guarantee for its application in repeated photothermal therapy.

[0075] (3) Detect and calculate the photothermal conversion efficiency of FGNRs.

[0076] The laser power density is fixed at 0.5 W / cm². 2 To ensure stable device parameters. At 0.5 W / cm 2 The sample was irradiated with a 1064nm laser at a high power density for 600 seconds, and the temperature was recorded by an infrared thermal imager at 10-second intervals to obtain the temperature curve for the heating stage. After 10 minutes of laser irradiation, the laser was immediately turned off, and the sample temperature was recorded by the infrared thermal imager at 10-second intervals until the sample temperature dropped to near room temperature. This process was the cooling stage, and the temperature data for the cooling stage was recorded to obtain the cooling curve. The temperature change rate dT / dt for this stage was calculated based on the heating curve, and combined with the total heat capacity C, the heat power absorbed by the sample was obtained as Q1 = C × dT / dt. The actual output power P of the laser was measured by a power meter, and combined with the absorption efficiency η of the sample to the 1064nm laser, the actual laser power absorbed by the sample was obtained as Q2 = P × η. The photothermal conversion efficiency η was calculated as: η = Q1 / Q2 × 100%, and the calculated photothermal conversion efficiency of FGNRs was 51%.

[0077] Using time as the x-axis and temperature as the y-axis, the temperature data from the heating and cooling stages are integrated to plot a complete heating-cooling curve. The calculation process and key parameters of the photothermal conversion efficiency are annotated on the graph. The results are as follows: Figure 4 As shown in Figure C, the curve clearly demonstrates the heating and natural cooling processes of FGNRs under laser irradiation, further verifying their efficient and stable photothermal conversion capabilities and providing important performance data support for subsequent tumor photothermal therapy applications.

[0078] II. Catalytic performance testing

[0079] (1) Detect the pH changes of FGNRs in glucose solution at different temperatures.

[0080] A 10 mM glucose aqueous solution was prepared, and FGNRs were dispersed in the glucose aqueous solution to prepare a 100 ppm FGNRs-glucose mixed solution. The solution was ultrasonically dispersed for 10 min to ensure homogeneity and stability. A 10 mM glucose aqueous solution without FGNRs was used as a blank control group.

[0081] Temperature gradients associated with mild photothermal therapy were selected and set at 25℃ (room temperature), 37℃ (physiological temperature), and 45℃, with three parallel experiments set up for each temperature group.

[0082] Take 5 mL of LGFNRs-glucose mixed solution and place it in a centrifuge tube. Place the tube in a constant temperature water bath at the corresponding temperature and keep it warm. Start timing after the solution temperature stabilizes. Use a precision pH meter to sample and measure the pH value every 50 seconds. After each sampling, quickly complete the test and put the sample back into the water bath to avoid temperature fluctuations. The total test time is 600 seconds. The blank control group is tested for pH value simultaneously under the same temperature conditions.

[0083] Plot the pH changes of the FGNRs-glucose mixed solution and the blank control group at different temperatures using time as the x-axis and pH change ΔpH as the y-axis. The results are as follows: Figure 5 As shown in Figure A, the pH value of the blank control group did not change significantly at various temperatures; however, the pH value of the FGNRs-glucose mixed solution gradually decreased over time, and the higher the temperature, the faster the pH decreased and the larger the final ΔpH. The pH decrease was most significant at 45℃. The results indicate that increasing the temperature can significantly enhance the activity of glucose oxidase loaded on the surface of FGNRs, accelerate the catalytic oxidation of glucose to produce acidic products, and the mild photothermal therapy temperature range (40-45℃) can effectively promote the acidification of the tumor microenvironment, providing suitable acidic conditions for the Fenton-like reaction.

[0084] (2) Detect the ESR (electron spin resonance) spectra of FGNRs in glucose solutions with different pH values.

[0085] The pH of a 10 mM glucose aqueous solution was adjusted with hydrochloric acid and sodium hydroxide to obtain glucose solutions with pH values ​​of 4.0, 5.0, 6.0, 6.5, and 7.4, respectively. FGNRs and DMPO (5,5-dimethyl-1-pyrrolline-N-oxide, ·OH scavenger) were added to each pH glucose solution to prepare a mixed system, wherein the concentration of FGNRs was 100 ppm and the concentration of DMPO was 100 mM. The mixture was ultrasonically dispersed for 5 min to achieve homogeneity.

[0086] All samples were incubated at a constant temperature of 37℃ for 30 min to ensure that GOx on the FGNRs surface fully catalyzes the glucose reaction to produce H2O2, while also providing reaction time for the Fenton-like reaction. The incubated samples were then transferred to ESR detection tubes and detected using an electron spin resonance spectrometer. The detection parameters were set as follows: central magnetic field 3480 G, sweep width 100 G, microwave power 10 mW, modulation frequency 100 kHz, modulation amplitude 1 G, and scan time 40 s. ESR spectra of the samples under different pH conditions were plotted with g value on the x-axis and signal intensity on the y-axis.

[0087] The results are as follows Figure 5 As shown in Figure B, the ·OH characteristic peak was most prominent in the ESR spectrum at pH 4.0, with the signal intensity reaching its highest value; at physiological pH 7.4, the ·OH signal was close to the detection limit. This result indicates that the Fenton-like reactivity of FGNRs is significantly pH-dependent. When the photothermal effect increases the local temperature, promoting glucose oxidase to catalyze the generation of more H2O2 and lowering the pH value, the Fenton-like reactivity of FGNRs can be further activated, thereby achieving continuous and efficient generation of ·OH.

[0088] (3) Detect the FGNRsESR spectrum with and without added H2O2 and glucose.

[0089] Six experimental groups were set up: Group 1: 100ppm FPNRs + 10mM Glu; Group 2: 100ppm FPNRs + 100μM H₂O₂; Group 3: 100ppm FPNRs + 10mM Glu + 100μM H₂O₂; Group 4: 100ppm FGNRs + 10mM Glu; Group 5: 100ppm FGNRs + 100μM H₂O₂; Group 6: 100ppm FGNRs + 10mM Glu + 100μM H₂O₂. All samples were incubated at 37℃ for 30 min to ensure that each reaction proceeded fully. Electron spin resonance spectroscopy was used for detection, and ESR spectra of the four experimental groups and the blank control group were plotted with g-value on the x-axis and signal intensity on the y-axis.

[0090] The results are as follows Figure 6 As shown in Figure A, the characteristic peak intensity of ·OH in the FGNRs+glucose+H2O2 reaction was significantly higher than that in other experimental groups, with clear and symmetrical peak shapes. This result indicates that glucose and H2O2 can synergistically promote the production of ·OH from FGNRs. Glucose generates H2O2 via GOx catalysis, providing a substrate for the Fenton-like reaction, while exogenous H2O2 further replenishes the substrate concentration. Together, they enhance the Fenton-like catalytic efficiency on the Fe2P substrate, verifying the synergistic mechanism of "GOx-based H2O2 production-Fe2P-catalyzed ·OH production".

[0091] (4) Detect the ESR spectra of FGNRs in glucose solutions at different temperatures.

[0092] Six experimental groups were set up: Group 1: 100 ppm FGNRs; Group 2: 100 ppm FGNRs + 10 mM glucose + 25℃; Group 3: 100 ppm FGNRs + 10 mM glucose + 37℃; and Group 4: 100 ppm FGNRs + 10 mM glucose + 45℃. The samples were incubated in constant temperature water baths at their respective temperatures for 30 min, and then transferred to ESR detection tubes for ESR detection. ESR spectra of the experimental groups and the blank control group at different temperatures were plotted with g-values ​​on the x-axis and signal intensity on the y-axis.

[0093] The results are as follows Figure 6 As shown in Figure B, the intensity of the ·OH characteristic peak gradually increases with increasing temperature, indicating that increasing temperature can significantly enhance the Fenton-like catalytic activity of FGNRs, especially the mild photothermal therapy temperature (40-45℃) can efficiently promote the generation of ·OH.

[0094] (5) Detect the fluorescence spectra of FGNRs in glucose solutions at different temperatures.

[0095] Prepare 10 mM glucose aqueous solution and 5 mM terephthalic acid (TA) aqueous solution; divide into 4 experimental groups:

[0096] Group 1: 100ppm FGNRs + 10mM glucose + 100μM H2O2 + 45℃

[0097] Group 2: 100ppm FGNRs + 10mM glucose + 45℃

[0098] Group 3: 100ppm FGNRs + 10mM glucose + 37℃

[0099] Group 4: 100ppm FGNRs + 10mM glucose + 25℃.

[0100] The samples were incubated in a constant-temperature water bath at the corresponding temperature for 60 min to ensure complete reaction between TA and ·OH. Subsequently, a fluorescence spectrophotometer was used for detection, with an excitation wavelength of 315 nm, an emission wavelength scanning range of 350-550 nm, both excitation and emission slits of 5 nm, and a photomultiplier tube voltage of 700 V. Fluorescence spectra of the experimental group and the blank control group at different temperatures were plotted with wavelength as the x-axis and fluorescence intensity as the y-axis.

[0101] The results are as follows Figure 6 As shown in Figure C, the experimental group exhibited the characteristic fluorescence peak of hydroxyterephthalic acid at 425 nm, and the fluorescence intensity showed a significant increasing trend with increasing temperature; the fluorescence intensity further increased after the addition of H2O2. This result is consistent with... Figure 6The ESR test results of B corroborate each other, further confirming that the temperature range of mild photothermal therapy (40-45℃) can significantly enhance the ability of FGNRs to generate ·OH, providing a reliable basis for the selection of temperature parameters for the synergistic treatment of mild photothermal and chemokinetics.

[0102] Example 3

[0103] This embodiment examines the in vitro antitumor effect of the nano-formulation prepared in Example 1.

[0104] Experiment 1: The cytotoxicity of different concentrations of FGNRs was investigated using the CCK-8 assay.

[0105] Human normal kidney cells HK-2 and HEK-293, and human renal cell carcinoma cells 786-O and OS-RC-2 were selected as models. Cells were grown at a density of 5 × 10⁶ cells per well. 3 The cells were seeded at a density of 1000 cells / well in 96-well plates. After 24 hours of culture and adhesion, the cells were treated with a fresh culture medium containing different concentrations of FGNRs (0, 25, 50, 100, 150, 200 ppm). After a specified culture time, 10 μL of LCK-8 solution was added to each well and incubated for 1-4 hours. The absorbance at 450 nm was then measured using a microplate reader.

[0106] The relative cell viability was measured as follows Figure 7 As shown, FGNRs exhibited low toxicity to both normal cell types, but showed significant inhibition against renal cell carcinoma at a concentration of 100 ppm.

[0107] Experiment 2: The cytotoxicity of FGNRs under different treatment conditions was investigated using the CCK-8 assay.

[0108] Using human renal cell carcinoma cells 786-O and OS-RC-2 as models, cells were grown at a density of 5 × 10⁶ cells per well. 3 The cells were seeded at a density of [number] cells per well in a 96-well plate, and after 24 hours of culture and adhesion, they were subjected to drug and / or near-infrared laser irradiation (NIR) treatment.

[0109] Ctrol group: Replace with fresh culture medium that does not contain FGNRs;

[0110] FPNRs group: Replace with fresh culture medium containing 100 ppm FPNRs;

[0111] FGNRs group: Replace with fresh culture medium containing 100 ppm FGNRs;

[0112] NIR group: The medium was replaced with fresh medium without FGNRs and irradiated with 1064nm near-infrared laser at a power density of 1.5W / cm² for 5 min.

[0113] FPNRs+NIR group: Replace with fresh culture medium containing 100 ppm FPNRs and apply 1064 nm near-infrared laser irradiation at a power density of 1.5 W / cm² for 5 min;

[0114] FGNRs+NIR group: Replace with fresh culture medium containing 100 ppm FGNRs and apply 1064 nm near-infrared laser irradiation at a power density of 1.5 W / cm² for 5 min;

[0115] After continuing the culture for the specified time, add 10 μL of LCK-8 solution to each well, incubate for 1-4 hours, and then measure the absorbance at 450 nm using a microplate reader.

[0116] The relative cell viability was measured as follows Figure 8 As shown, compared with the control group, cell activity did not decrease significantly when treated with FPNRs, FGNRs or NIR alone; however, the activity of both cell lines decreased significantly after combined near-infrared laser irradiation, especially the combination of FGNRs and NIR, indicating that FGNRs have photothermal therapeutic effects and exhibit stronger anti-tumor activity when combined with near-infrared laser.

[0117] Experiment 3: The cytotoxicity of FGNRs under different pH conditions was investigated using the CCK-8 assay.

[0118] Using human renal cell carcinoma OS-RC-2 as a model, cells were grown at a density of 5 × 10⁶ cells per well. 3 Inoculated at a density of [number] cells per well in 96-well plates, after 24 hours of culture and adhesion, drug treatment was performed under different pH conditions:

[0119] FPNRs (pH 7.4) group: Replace with fresh culture medium containing 100 ppm FPNRs at pH 7.4;

[0120] FPNRs (pH 6.5) group: Replace with fresh culture medium containing 100 ppm FPNRs at pH 6.5;

[0121] FGNRs (pH 7.4) group: Replace with fresh culture medium containing 100 ppm FGNRs at pH 7.4;

[0122] FGNRs (pH 6.5) group: Replace with fresh culture medium containing 100 ppm FGNRs at pH 6.5;

[0123] After continuing the culture for the specified time, add 10 μL of LCK-8 solution to each well, incubate for 1-4 hours, and then measure the absorbance at 450 nm using a microplate reader.

[0124] The relative cell viability was measured as follows Figure 9As shown in Figure A, the relative cell viability was lower at pH 6.5, and the cell inhibition rate of the FGNRs group was higher than that of the FPNRs group at pH 6.5, indicating that FGNRs are more toxic to renal cell carcinoma cells in an acidic environment. This is consistent with the result that FGNRs have enhanced Fenton-like catalytic activity under acidic conditions, further verifying that tumor microenvironment acidification can promote the chemokinetic therapeutic effect of FGNRs.

[0125] Experiment 4: The cytotoxicity of FGNRs at different glucose concentrations was investigated using the CCK-8 assay.

[0126] Using human renal cell carcinoma OS-RC-2 as a model, cells were grown at a density of 5 × 10⁶ cells per well. 3 In 96-well plates, the cells were seeded at a density of [number] cells / wells. After 24 hours of culture and adherence, the cells were treated with different glucose concentrations.

[0127] Low glucose concentration group: Replace with fresh culture medium containing 100 ppm FGNRs and 10 mM glucose;

[0128] High glucose concentration group: Replace with fresh medium containing 100 ppm FGNRs and 25 mM glucose;

[0129] After continuing the culture for the specified time, add 10 μL of LCK-8 solution to each well, incubate for 1-4 hours, and then measure the absorbance at 450 nm using a microplate reader.

[0130] The relative cell viability was measured as follows Figure 9 As shown in Figure B, the cells in the high glucose concentration group had relatively lower viability, indicating that the toxicity of FGNRs to renal cancer cells increased with increasing glucose concentration. This further verifies that glucose, as a GOx substrate, can promote H2O2 generation, thereby enhancing the cell-killing effect mediated by the Fenton-like reaction. This suggests that the high glucose metabolism characteristics of tumor cells can synergistically enhance the chemokinetic efficacy of FGNRs.

[0131] The above experimental results show that the cell-killing effect of FGNRs is further enhanced in near-infrared laser, acidic or high-glucose environments, confirming the effectiveness of its synergistic therapy.

[0132] Experiment 5: Calcein-AM / PI fluorescence spectra were used to investigate the cytotoxicity of FGNRs.

[0133] Using human renal cell carcinoma OS-RC-2 as a model, cells were grown at a density of 5 × 10⁶ cells per well. 3Cells were seeded at a density of [number] cells / well in 96-well plates and cultured for 24 hours until adherence. Then, cells were treated with drugs and / or near-infrared laser (NIR) irradiation, following the same grouping and treatment methods as in Experiment 2 of this embodiment. After drug and NIR treatment, cells were cultured for another 24 hours. The culture medium in the wells was discarded, and the cells were washed twice with PBS. Premixed Calcein-AM / PI working solution (enough to cover the cells) was added to each well, and the cells were incubated at 37°C in the dark for 15-20 minutes. After incubation, the cells were washed with PBS and immediately observed under a fluorescence microscope: live cells were observed using the FITC channel (green fluorescence), and dead cells were observed using the PI channel (red fluorescence).

[0134] The results are as follows Figure 10 As shown, the cells in the control, FPNRs, FGNRs, and NIR groups were mainly green fluorescent live cells, while the FPNRs+NIR and FGNRs+NIR groups showed a large number of red fluorescent dead cells. The proportion of dead cells in the FGNRs+NIR group was significantly higher than that in the FPNRs+NIR group, indicating that the combined treatment of the material and NIR can effectively kill cells, and the photothermal / photodynamic killing effect of FGNRs is better.

[0135] VI. Activated carbon fluorescence imaging was used to investigate the effect of FGNRs on ROS induction.

[0136] Using human renal cell carcinoma OS-RC-2 as a model, cells were grown at a density of 5 × 10⁶ cells per well. 3 Cells were seeded at a density of [number] cells per well in 96-well plates and cultured for 24 hours until adherence. Then, they were treated with drugs and / or near-infrared laser (NIR) irradiation, following the same grouping and treatment methods as in Experiment 2 of this embodiment. After drug and NIR treatment, the cells were cultured for another 24 hours. The culture medium in the wells was discarded, and the cells were washed twice with PBS. ROS probe working solution was added, and the cells were incubated at 37°C in the dark for 20 minutes. After washing with PBS, the cells were observed under a fluorescence microscope, and the average fluorescence intensity of the cells was calculated using image analysis software.

[0137] The results are as follows Figure 11 As shown, cells in the control, FPNRs, FGNRs, and NIR groups showed only weak green fluorescence, indicating that the ROS level induced by a single treatment was extremely low. The green fluorescence of the FPNRs+NIR and FGNRs+NIR groups was significantly enhanced, and the fluorescence intensity of the FGNRs+NIR group was even higher, indicating that the combined treatment can induce a large amount of ROS production, thereby achieving efficient ROS enrichment in the tumor microenvironment, laying an important foundation for subsequent anti-tumor therapy.

[0138] Example 4

[0139] This embodiment examines the in vivo antitumor efficacy and biosafety of the nano-formulation prepared in Example 1.

[0140] I. Constructing an animal model

[0141] A nude mouse model of BALB / c renal cell carcinoma bearing 786-O tumors was established using the following methods:

[0142] Female BALB / c nude mice aged 4-6 weeks and weighing 18-22g were selected and acclimatized for one week under specific pathogen-free conditions. 786-O renal cell carcinoma cells in the logarithmic growth phase were digested with trypsin, counted, and resuspended in sterile PBS to adjust the cell density to 1×10⁻⁶. 8 Cells / mL. Each nude mouse was subcutaneously inoculated with 100 μL of this cell suspension (containing 1 × 10⁶ cells / mL) on its right back. 7 (Number of cells). Mice were observed daily for their condition, and tumor volume was measured periodically until the tumor reached approximately 100 mm². 3 At that time, it was considered that the tumor-bearing model had been successfully established.

[0143] II. Grouping and Processing:

[0144] Control group: Injected with an equal volume of PBS buffer via tail vein;

[0145] NIR group: An equal volume of PBS buffer was injected into the tail vein, and 8 hours after injection, the tumor site was irradiated with a 1064nm laser at 0.3W / cm² for 10 minutes.

[0146] FPNRs group: FPNRs were injected via tail vein at a dose of 5 mg / kg;

[0147] FGNRs group: FGNRs were injected via tail vein at a dose of 5 mg / kg;

[0148] FPNRs+NIR group: FPNRs were injected via tail vein at a dose of 5 mg / kg. Eight hours after injection, the tumor site was irradiated with a 1064 nm laser at 0.3 W / cm² for 10 min.

[0149] FGNRs+NIR group: FGNRs were injected via tail vein at a dose of 5 mg / kg. Eight hours after injection, the tumor site was irradiated with a 1064 nm laser at 0.3 W / cm² for 10 min.

[0150] III. Examine the infrared thermography and temperature changes of mice in the NIR group and FGNRs+NIR group at different time intervals.

[0151] The results are as follows Figure 12As shown, the temperature in the NIR-only irradiation group did not increase significantly within 10 minutes, and the thermal imaging remained predominantly low-temperature blue. In the FGNRs+NIR group, the yellow / red hot zone gradually expanded and its brightness increased with the extension of irradiation time, and the temperature continued to rise over time, with the tumor temperature reaching 45℃, which was significantly higher than that in the NIR-only irradiation group. This indicates that FGNRs have excellent photothermal conversion performance and can effectively convert NIR light energy into heat energy.

[0152] IV. Examine the changes in body weight of mice in each group.

[0153] The body weight of mice in each group was monitored within 14 days after laser irradiation, and the results are as follows: Figure 13 As shown, the body weight of mice in each group increased over 14 days, and there was no significant difference in body weight change among the groups. This indicates that the materials used, FPNRs, FGNRs, and NIR irradiation, did not cause significant toxicity to the animals. The combined treatment of FPNRs, FGNRs, and NIR showed good biocompatibility and did not affect the normal growth of the animals.

[0154] V. To examine the in vivo tumor treatment efficacy of FGNRs.

[0155] Tumor volume and weight changes in mice were monitored within 14 days after laser irradiation. Mice were sacrificed 14 days later, and tumors were isolated. Results are as follows: Figure 14 and Figure 15 As shown, the tumor volume in the control, NIR, FPNRs, and FGRNs groups increased significantly over time, with the control and NIR groups exhibiting the heaviest tumor weight. The tumor volume growth in the FPNRs+NIR and FGNRs+NIR groups was significantly slowed, with the FGNRs+NIR group showing the most significant inhibitory effect, achieving a tumor inhibition rate as high as 96.3%, and a significant reduction in tumor weight. This result indicates that combined treatment with FGNRs and NIR has a significant inhibitory effect on tumors in vivo.

[0156] VI. The safety of FGNRs was investigated through acute toxicity and subacute toxicity tests.

[0157] Fourteen days after treatment, tumor-bearing mice were sacrificed, and tumor tissue was collected, fixed, embedded, and sectioned. H&E staining was used to observe the morphology and structure of the tumor tissue; TUNEL staining was used to detect tumor cell apoptosis; Ki-67 staining was used to detect tumor cell proliferation activity; and the stained sections were observed and images were acquired using an optical microscope.

[0158] The results are as follows Figure 16 As shown, H&E staining results indicated that the tumor tissue cells in the control group and the single treatment groups (FPNRs, FGNRs, NIR) were dense and structurally intact; while the tumor tissue cells in the FPNRs+NIR and FGNRs+NIR groups showed decreased density and loose structure, suggesting significant cell damage.

[0159] TUNEL staining results showed that the FGNRs+NIR group had significantly more positive staining signals (apoptotic cells) than other groups, indicating that the tumor cells in this group had a higher level of apoptosis.

[0160] Ki-67 staining results showed that the Ki-67 positive signal (proliferating cells) in the FGNRs+NIR group was significantly reduced, indicating that the proliferation activity of tumor cells in this group was significantly inhibited.

[0161] VII. The safety of FGNRs was investigated through acute toxicity and subacute toxicity tests.

[0162] No mouse deaths were observed in the acute toxicity test (dose up to 80 mg / kg). The subacute toxicity test (weekly injections for 4 weeks) showed no significant abnormalities in blood routine tests, blood biochemistry, and H&E staining of major organs.

[0163] Example 5

[0164] This example examines the in vitro and in vivo imaging performance of the nanoformulation prepared in Example 1.

[0165] I. In vitro imaging performance testing

[0166] 1. MRI (T2-weighted imaging):

[0167] FGNRs dispersions with different Fe concentrations (0, 13.09, 26.17, 52.34, 104.69, 209.38 μM) were prepared, and in vitro T2-weighted images were acquired using a magnetic resonance imaging system. At the same time, the T2 relaxation time at each concentration was measured, and the T2 relaxation rate was obtained by fitting.

[0168] The results are as follows Figure 17 As shown in Figure A, the T2-weighted signal of the FGNRs dispersion gradually decreases with increasing Fe concentration. Figure 17 B shows a strong linear negative correlation between T2 relaxation time and Fe concentration, with an r2 value of 145.3 mM obtained from the fitting. -1 s -1 This indicates that FGNRs have excellent T2-weighted MRI imaging performance.

[0169] 2. PAI (Photoacoustic Imaging):

[0170] FGNRs dispersions with different concentrations (3.9, 7.8, 15.6, 31.3, 62.5 ppm) were prepared, and photoacoustic images were acquired at wavelengths of 808 nm (near-infrared I) and 1064 nm (near-infrared II), respectively. The relationship between photoacoustic amplitude and concentration was quantitatively analyzed.

[0171] Photoacoustic images acquired at 808nm, such as Figure 18As shown in Figure A, the curve of photoacoustic signal increasing with concentration is as follows: Figure 18 As shown in B, the acoustic image acquired at 1064nm is as follows: Figure 19 As shown in Figure A, the curve of photoacoustic signal increasing with concentration is as follows: Figure 19 As shown in Figure B, at wavelengths of 808 nm and 1064 nm, the photoacoustic signals of FGNRs both increase with increasing concentration; the linear fitting result R² is close to 1, indicating that the photoacoustic amplitude is significantly positively correlated with the concentration, verifying the concentration-dependent photoacoustic response characteristics of FGNRs in the near-infrared I / II region.

[0172] II. In vivo imaging performance testing

[0173] 1. MRI imaging:

[0174] Mice bearing 786-O renal cell carcinomas were injected via tail vein at a dose of 5 mg / kg; FGNRs were also injected intratumorally at a dose of 5 mg / kg. T2-weighted magnetic resonance images of the tumor site were acquired before and after injection to observe signal changes in the tumor region.

[0175] The results are as follows Figure 20 As shown, after FGNRs injection, the T2-weighted signal of the tumor site (red circle) was significantly enhanced, indicating that FGNRs can be targeted and enriched in vivo to enhance the MRI signal of the tumor area.

[0176] 2. PAI imaging:

[0177] After tumor-bearing mice were injected intratumorally or via the tail vein, photoacoustic images of the tumor site were collected at 0, 2, 4, 8, 12, and 24 hours, and the photoacoustic amplitude at different time points was quantitatively analyzed.

[0178] The results are as follows Figure 21 and Figure 22 As shown, the photoacoustic amplitude at the tumor site first increased and then decreased over time, reaching a peak at 8 hours in the intravenous injection group. This result provides an optimal time window for subsequent laser treatment and demonstrates that FGNRs can effectively accumulate at the tumor site in vivo and generate photoacoustic signals.

[0179] FGNRs can be used for dual-mode MRI / PAI imaging diagnosis of tumors, providing crucial imaging support for precise preoperative tumor localization, intraoperative navigation, and postoperative efficacy follow-up. The combined application of MRI and PAI can clearly present the anatomical structure of the tumor and reflect its physiological metabolic characteristics, laying the foundation for early tumor diagnosis and personalized treatment planning.

Claims

1. A nanoformulation based on ferrous phosphide nanostructures, characterized in that, The core layer is a hydrophobic ferrous phosphide nanostructure, the modification layer is a PTMP-PMAA polymer, the PTMP-PMAA polymer is coated on the surface of the hydrophobic ferrous phosphide nanostructure, and the functional layer is glucose oxidase which is covalently grafted on the surface of the modification layer PTMP-PMAA polymer through an amidation reaction.

2. The nanoformulation based on ferrous phosphide nanostructures as claimed in claim 1, wherein, The hydrophobic ferrous phosphide nanostructure is a nanorod, the length of the nanorod is 150-200 nm, and the diameter of the nanorod is 8-15 nm.

3. A method for preparing a nanoformulation based on ferrous phosphide nanostructures according to claim 1 or 2, characterized in that, The steps are as follows: Step one, preparing the hydrophobic ferrous phosphide nanostructure: Dissolve acetylacetone iron in an oleylamine solvent, complete the growth of the nanostructure at a first heating temperature under the protection of inert gas, then add tri-octyl phosphine, increase the temperature of the reaction system to a second heating temperature, and continue to react to obtain the hydrophobic ferrous phosphide nanostructure; Step two, preparing the PTMP-PMAA polymer: Under the protection of inert gas, stir and dissolve methacrylic acid, anhydrous ethanol and pentaerythritol tetra-3-mercaptopropionate, increase the temperature to a third heating temperature, then add a free radical initiator to initiate the copolymerization reaction, concentrate, precipitate and vacuum dry after the reaction to obtain the PTMP-PMAA polymer; Step three, preparing the nano preparation loaded with glucose oxidase: Disperse the hydrophobic ferrous phosphide nanostructure prepared in step one and the PTMP-PMAA polymer prepared in step two in anhydrous ethanol, ultrasonically treat and stir overnight, and centrifuge to obtain the PTMP-PMAA polymer coated ferrous phosphide nanostructure; Disperse the obtained PTMP-PMAA polymer coated ferrous phosphide nanostructure in a MES buffer solution with a pH value of 5.0-5.5, add carbodiimide and N-hydroxysuccinimide salt, then adjust the pH value of the system to 7.0-8.0 and add glucose oxidase, stir overnight under ice bath condition, and centrifuge to obtain the nano preparation loaded with glucose oxidase.

4. The method of claim 3, wherein the phosphorous-based nano-formulation is prepared by the steps of: The molar ratio of acetylacetone iron to tri-octyl phosphine in step one is 1:8-12; when preparing the ferrous phosphide nanorod, the mass-volume ratio of acetylacetone iron to oleylamine solvent is 3.0-4.0 mg:1 mL, and the oleylamine solvent is added in two equal volumes.

5. The method of claim 4, wherein the phosphorous-based nano-formulation is prepared by the steps of: The first heating temperature in step one is 250-270 DEG C, and the growth time of the nanostructure is 0.8-1.2 h; the second heating temperature is 310-330 DEG C, and the reaction time at the second heating temperature is 2-3 h.

6. The method of claim 5, wherein the phosphorous-based nano-formulation is prepared by the steps of: The molar ratio of methacrylic acid to pentaerythritol tetra-3-mercaptopropionate in step two is 60-80:1, and the mass-volume ratio of the total mass of methacrylic acid and pentaerythritol-3-mercaptopropionate to anhydrous ethanol is 0.10-0.15 mg:1 mL; The free radical initiator is azobisisobutyronitrile, and the amount of the azobisisobutyronitrile is 0.5-0.2% of the total moles of methacrylic acid and pentaerythritol-3-mercaptopropionate; and the third heating temperature is 70-80 DEG C.

7. The method for preparing nano-formulations based on ferrous phosphide nanostructures according to claim 6, characterized in that, The mass-volume ratio of the hydrophobic ferrous phosphide nanostructure, the PTMP-PMAA polymer and anhydrous ethanol in step three is 1 mg:0.5-2 mg:5 mL; the power of the ultrasonic is 80-120 W, and the ultrasonic time is 4-6 h.

8. The method for preparing the nano-formulation based on ferrous phosphide nano-structures according to claim 7, characterized in that, The mass-volume ratio of the PTMP-PMAA polymer coated ferrous phosphide nanostructure and the MES buffer in step three is 0.5-2 mg:1 mL; the added amount of the carbodiimide is 10 mM, the added amount of the N-hydroxysulfosuccinimide salt is 5 mM; the final concentration of the glucose oxidase in the reaction system is 1-3 mg / mL.

9. Use of the ferrous phosphide nanostructure based nano-preparation according to claim 1 or 2 in the preparation of a preparation for tumor synergistic therapy or an MRI / PAI contrast agent.

10. Use according to claim 9, characterized in that, The tumor synergistic therapy includes photothermal therapy, chemical dynamics therapy or starvation therapy.

Citation Information

Patent Citations

  • Protein self-assembled iron-based nanoparticle, preparation method thereof and application of protein self-assembled iron-based nanoparticle in anti-tumor drug delivery system

    CN111388451A

  • Construction and application of catalytic nanoparticles based on glucose oxidase / iron phosphate

    CN111450270A

  • Double-enzyme nano diagnosis and treatment agent as well as preparation method and application thereof

    CN114917339A

  • Exosome ferroferric oxide nanoprobe as well as preparation method and application thereof

    CN116370656A

  • Nanoparticles for synergistically treating tumors and preparation method thereof

    CN120960424A